Tratti estetici e omologie strutturali: verso un’estetica animale comparata - Bartalesi, Lorenzo (Scenari, 2024)
Starting from the observation that the contemporary evolutionary approach fails to exhaust the richness of animal aesthetic phenomena, the article is intended as a first contribution, in the direction of comparative animal aesthetics, to a nascent field of investigation in need of a broader interpretative pluralism. After a brief presentation of the main criticisms of evolutionary aesthetics, the problematic extension of human aesthetics to non-human animals is reformulated in the light of a radical recognition of the variability and plurality of animal aisthesis. A definition of aesthetics as a faculty with multiple components will then open up the possibility of a comparative approach that will be applied in the analysis of a case study.